Perancangan Mesin Automatic PTFE Tape Wrapper untuk Kebutuhan Perekatan Katup LPG 1/2 inch hingga 3/4 inch - Muhammad Rizal Ardiansyah; Dadan Heryada Wigenaputra; Dwiky Maulana Atmadji (Universitas Muhammadiyah Metro, 2026)
PTFE tape is an additive material used in fastening processes, particularly on threads or screw joints. Its function is to provide sealing properties ensuring tightness and leak prevention at the bonded interface. One notable application is found at a gas cylinder maintenance facility operating under direct authorization from PT. Pertamina. This facility targets a daily operational capacity of handling thousands of Liquefied Petroleum Gas (LPG) cylinders. However, the seal tape installation on each valve is still performed manually, which presents several operational challenges in terms of efficiency and consistency. This research focuses on designing an automated device for seal tape application. The primary objective is to develop an automatic seal tape wrapper machine to optimize the sealing process in terms of speed and reliability. To achieve this, the design process follows the VDI 2206 methodology from the Verein Deutscher Ingenieure (Association of German Engineers) and utilizes the 3D modeling software SolidWorks. The final outcome is a PTFE tape machine capable of operating automatically with a cycle time of 5-6 seconds per valve, and a production capacity of up to 3,900 valves per day.